COMPARISON OF EMERGENCE TIME AFTER TOTAL INTRAVENOUS ANAESTHESIA VERSUS INHALATIONAL ANAESTHESIA IN GYNAECOLOGICAL PROCEDURES: Anaesthesia in Gynaecological Procedures - Rizvi, Sqn Ldr Syed Ali Mazhar; Haq, Muhammad Ehsan -Ul-; ., Sakina Jaffery (Pakistan Armed Forces Medical Journal, 2013)
Objectives: To compare emergence time after Total Intra-venous Anesthesia (TIVA) using Propofol and Inhalational Anesthesia using Sevoflurane in minor gynecological and obstetric procedures.Study Design: Randomized controlled study.Place and Duration of Study: Department of Anesthesiology, Intensive Care and Pain Management, Combined Military Hospital, Peshawar. Six months from 15th March 2010 to 14th September 2010.Patients and Methods: A total of 200 gynecological patients of ASA-I and II were included in this study. Patients were divided randomly in 2 groups of 100 each using random numbers table. Group A patients were administered TIVA- Propofol and group B patients were given inhalational anaesthesia using Sevoflurane. A stopwatch was started when the anesthetic drug was discontinued at the end of surgery and was stopped as soon as the patient opened her eyes spontaneously to record the emergence time. All the data was entered in a patient performa.Results: It was observed that group A patients who were administered Propofol had a faster emergence time as compared to group B patients who were administered Sevoflurane. The mean emergence time of TIVA- Propofol group was 6.24 minutes (SD=0.726) while that of inhalational- Sevoflurane group was 8.52 minutes (SD=1.218). The shorter emergence time of Propofol group was highly significant when compared with the Sevoflurane group (p